Multi-state outcome analysis of treatment interventions after failure of non-surgical root canal treatment: a 13-year retrospective study - Bhagavatula, Pradeep; Moore, Alex; Rein, Lisa; Szabo, Aniko; Ibrahim, Mohamed (Journal of Applied Oral Science, 2021)
Objective: To examine the factors affecting the transitions through treatment interventions after failure of non-surgical root canal treatment (NS-RCT). Methodology: Insurance enrollment and claim information for enrollees of Delta Dental of Wisconsin (DDWI), USA were analyzed for 438,487 initial NS-RCT procedures to determine the effect of initial provider type and other covariates on additional treatments (no additional treatment, nonsurgical retreatment, surgical retreatment and extraction). A multi-state model was created using the “mstate” R package. Transitions between the four states identified by Code on Dental Procedures and Nomenclature were analyzed. Cox proportional Hazards regression stratified by transition type was used to estimate the effect of provider type on the risk of each transition, adjusting for covariates. Results: The overall survival rates for all teeth that were treated by NS-RCT was 82.8% [95% CI 82.57%, 83.11%] at 10 years. Approximately, 7% of cases changed from the first state of initial NS-RCT during the 13-year study period with ultimately 0.9%, 0.4% and 5% of cases receiving non-surgical retreatment, surgical retreatment or extraction, respectively. Teeth are more likely to be retreated non-surgically than surgically, and to be extracted than retreated. In general, the probability of a tooth having non-surgical retreatment was higher if the initial provider was not an endodontist (Hazard Ratio (HR)=3.2). Molars were more likely to be non-surgically retreated (HR=2.0) or extracted (HR=2.8) when compared to anterior teeth. The probability of non-surgical retreatment (HR=0.93) or extraction (HR=0.50) was lower when a crown was placed within 90 days after NS-RCT. Conclusion: Most teeth remained in the same state after treatment with no additional treatment transitions. When a transition occurred, it was more likely to be an extraction. Type of provider, age, location of the tooth, gender, and time to placement of final restoration significantly influence treatment transitions.